Retenção acadêmica nos cursos de Licenciatura em Ciências da Natureza da UNIPAMPA - (:unkn) unknown (Universidade Federal do Pampa, 2016)
The objective of this study was to investigate the possible factors related to academic retention in undergraduate courses in Nature Sciences (LCN) of the Federal University of Pampa (Unipampa), academic units of Dom Pedrito and Uruguaiana. The study consisted of a field survey which was developed in two stages. In the first one, we identified the curricular components that presented the highest failure rate and enrollment in the year 2016. In the second stage, the retention was investigated with the academics who have already failed and / or locked their enrollments at least, in a component of the course. In order to collect the data, a structured questionnaire with closed questions, multiple choice and affirmations was elaborated. These should be evaluated for their influence on academic retention through a five-degree scale related to personal factors, both internal and external to the institution. From the analyzes by mixed methods, it was identified that the components with the highest index of reprobations and locking of the enrollment in the course of Dom Pedrito were the followng: Universe: Structure and Organic Matter of the Earth, both with 33 cases. For the LCN of the campus of Uruguaiana were the followng: Universe in evolution and structure of matter (32) and Universe in evolution and structure of matter II (22). The main factors that influence academic retention in the two campuses were evidenced: the insufficient training obtained in High School; existence of difficult to understand components; lack of student performance support programs; need to work while attending the course; among others.
Keywords: Formação de professores; Permanência prolongada; Reprovações e trancamentos; Teacher training; Prolonged permanence; Reprocessing and locking; CNPQ::CIENCIAS EXATAS E DA TERRA